Striatal D1 Dopamine Neuronal Population Dynamics in a Rat Model of Levodopa-Induced Dyskinesia - Gao, Shasha; Gao, Rui; Yao, Lu; Feng, Jie; Liu, Wanyuan; Zhou, Yingqiong; Zhang, Qiongchi; Wang, Yong; Liu, Jian (Frontiers in Aging Neuroscience, 2022)
Background: The pathophysiology of levodopa-induced dyskinesia (LID) in Parkinson’s disease (PD) is not well understood. Experimental data from numerous investigations support the idea that aberrant activity of D1 dopamine receptor-positive medium spiny neurons in the striatal direct pathway is associated with LID. However, a direct link between the real-time activity of these striatal neurons and dyskinetic symptoms remains to be established. Methods: We examined the effect of acute levodopa treatment on striatal c-Fos expression in LID using D1-Cre PD rats with dyskinetic symptoms induced by chronic levodopa administration. We studied the real-time dynamics of striatal D1+ neurons during dyskinetic behavior using GCaMP6-based in vivo fiber photometry. We also examined the effects of striatal D1+ neuronal deactivation on dyskinesia in LID rats using optogenetics and chemogenetic methods. Results: Striatal D1+ neurons in LID rats showed increased expression of c-Fos, a widely used marker for neuronal activation, following levodopa injection. Fiber photometry revealed synchronized overactivity of striatal D1+ neurons during dyskinetic behavior in LID rats following levodopa administration. Consistent with these observations, optogenetic deactivation of striatal D1+ neurons was sufficient to inhibit most of the dyskinetic behaviors of LID animals. Moreover, chemogenetic inhibition of striatal D1+ neurons delayed the onset of dyskinetic behavior after levodopa administration. Conclusion: Our data demonstrated that aberrant activity of striatal D1+ neuronal population was causally linked with real-time dyskinetic symptoms in LID rats.